Morphology of enkephalin-immunoreactive myenteric neurons in the human gut - Brehmer, Axel; Lindig, Tobias; Schrödl, Falk; Neuhuber, Winfried; Ditterich, Daniel; Rexer, Martin; Rupprecht, Holger (Histochemistry and Cell Biology, 2005)
The aim of this study was the morphological and further chemical characterisation of neurons immunoreactive for leu-enkephalin (leuENK). Ten wholemounts of small and large intestinal segments from nine patients were immunohistochemically triple-stained for leuENK/neurofilament 200 (NF)/substance P (SP). Based on their simultaneous NF-reactivity and 3D reconstruction of single NF-reactive cells, 97.5% of leuENK-positive neurons displayed the appearance of stubby neurons: small somata; short, stubby dendrites and one axon. Of these leuENK-reactive stubby neurons, 91.3% did not display co-reactivity for SP whereas 8.7% were SP-co-reactive. As to their axonal projection pattern, 50.4% of the recorded leuENK stubby neurons had axons running orally whereas in 29.4% they ran anally; the directions of the remaining 20.2% could not be determined. No axons were seen to enter into secondary strands of the myenteric plexus. Somal area measurements revealed clearly smaller somata of leuENK-reactive stubby neurons (between 259±47 μm and 487±113 μm) than those of putative sensory type II neurons (between 700±217 μm and 1,164±396 μm). The ratio dendritic field area per somal area of leuENK-reactive stubby neurons was between 2.0 and 2.8 reflecting their short dendrites. Additionally, we estimated the proportion of leuENK-positive neurons in comparison to the putative whole myenteric neuron population in four leuENK/anti-Hu doublestained wholemounts. This proportion ranged between 5.9% and 8.3%. We suggest leuENK-reactive stubby neurons to be muscle motor neurons and/or ascending interneurons. Furthermore, we explain why we do not use the term "Dogiel type I neurons" for this population. © Springer-Verlag 2005.
Keywords: 3D reconstruction; Enteric nervous system; Innervation; Intestine; Opioids